Science and Technology for Sustainable Development : Solutions for Global Challenges - Kartik Aryan Mishra; Rohan Pratap Singh (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
Science and technology have the potential to provide innovative solutions to global sustainability challenges, including climate change, resource depletion, and public health issues. This paper explores the role of scientific innovation in achieving sustainable development goals (SDGs), focusing on renewable energy technologies, waste management innovations, and sustainable agriculture practices. The study highlights successful global case studies where science and technology have been used to address pressing environmental and social issues.